Estudo sobre acetilação da isoniazida em pacientes com tuberculose pulmonar e da sua implicação na redução ou eliminação da carga bacilar no escarro - Chiabai, Maria José (2013)
N-acetyltransferase 2 is the main enzyme responsible for the metabolism and inactivation of isoniazid in humans. Mutations in the gene NAT2 lead to 3 profiles of acetylation genotype that modify serum levels of the drug: slow acetylators, intermediate and fast, which can change the therapeutic outcome. The aim of the study was to investigate whether different profiles can influence the time of negativation sputum culture, and if there is a correlation between bacterial load and disease severity with time to culture conversion. The study population comprised 62 patients who had their DNAs sequenced for identification of mutations in the gene NAT2 and to determine the acetylation. Genotypic analysis detected 10 SNPs, and SNPs 341 T>C (39.65%) and 481 C>T (38.71%) were the most frequent. The determination of allelic variants identified NAT2*5B (29.03%), NAT2*6A (23.39%) and NAT2*4 (24.19%) as alleles more frequent and NAT2*5B/5B as the most frequent genotype (20.4%). Among 62 patients, it was possible to correlate time of negative culture and acetylation profile of 43 them, which 58.3% and 55.6% had genotype slow with greater frequency in month 1 and months 3, respectively. Through microbiological data, the bacterial load and severity of disease were also compared with the time of negativation, indicating that patients with moderate or advanced disease (76.7%) and those with high bacterial load (60.4%) had no statistical association with the conversion time of culture. Finally, growth curves of strains of M. tuberculosis of patients were constructed to evaluate possible differences in the duration of the lag phase between the isolates, but there was no statistical difference between them. Based on these results, it is found that there is no association between the profile acetylation of the patient, bacterial load and the severity of the illness and the time of negative sputum cultures